2023
DOI: 10.1590/1806-9282.20230314
|View full text |Cite
|
Sign up to set email alerts
|

Does resveratrol reduce cisplatin-induced ovarian damage?

Baris Ciplak,
Eyup Gokhan Turmus,
Ozlem Kara
et al.

Abstract: SUMMARY OBJECTIVE: The objective of this study was to investigate the protectiveness of resveratrol on cisplatin-induced damage to the ovary using experimental models. METHODS: A total of 30 female Wistar-Albino rats constituted the research material. The rats were categorized into three groups: Group 1 was administered one milliliter of 0.9% NaCl solution, Group 2 was administered 7.5 mg/kg cisplatin, and Group 3 was administered 7.5 mg/kg cisplatin and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…CDDP use may result in ovarian hypoplasia or exhaustion ( Meirow, 2000 ; Rossi et al, 2017 ). Ciplak et al (2023) showed that RES prevents and attenuates CDDP toxicity in ovarian follicles by increasing superoxide dismutase and catalase levels and decreasing malondialdehyde levels in OC tissue. Similar results were obtained by Chinwe et al (2018) , who hypothesized that RES promotes follicle-stimulating hormone expression.…”
Section: Combined With Antitumor Drugs Res Increases Efficacy and Red...mentioning
confidence: 99%
“…CDDP use may result in ovarian hypoplasia or exhaustion ( Meirow, 2000 ; Rossi et al, 2017 ). Ciplak et al (2023) showed that RES prevents and attenuates CDDP toxicity in ovarian follicles by increasing superoxide dismutase and catalase levels and decreasing malondialdehyde levels in OC tissue. Similar results were obtained by Chinwe et al (2018) , who hypothesized that RES promotes follicle-stimulating hormone expression.…”
Section: Combined With Antitumor Drugs Res Increases Efficacy and Red...mentioning
confidence: 99%